Circadian Rhythm and Health : Influence of Food Intake Timing and Regular Exercise - Kyung-won Lee; Seung Kyum Kim (Korea Institute of Sport Science, 2023)
Circadian rhythm (CR) is an intrinsic process that changes in a cycle of approximately 24h/day to maintain body homeostasis. It is mainly controlled by the central command through the suprachiasmatic nucleus, and modern society features can disturb the central CR, contributing to various diseases. Recent studies have provided evidence that extrinsic factors, such as regular physical activity (RPA) and timerestricted feeding (TRF), can also alter the CR peripherally, emphasizing RPA and TRF as the non-therapeutic methods for circadian misalignment (CM). Therefore, this review scrutinizes the regulatory mechanism of CR and summarizes the relationships between CM and various diseases. In addition, by reviewing studies investigating the prevention or improvement of CM via RPA and TRF, the value of circadian biology research that can directly affect health, physical function, and lifespan is summarized. By introducing the scientific evidence for RPA and TRF to maintain and improve CR, we tried to emphasize the importance of regular exercise and healthy eating habits to people in the modern world who have difficulty maintaining CR.